2020
DOI: 10.2147/rmhp.s243207
|View full text |Cite
|
Sign up to set email alerts
|

<p>Unattended Pregnancies and Perinatal Mortality in Georgia</p>

Abstract: Introduction: The majority of pregnant women in Georgia attend the free-of-charge, national antenatal care (ANC) programme, but over 5% of pregnancies in the country are unattended. Moreover, Georgia has one of the highest perinatal mortality (PM) rates in Europe (11.7/1000 births). Purpose: To assess the association between unattended pregnancies and the risk of PM. Methods: Data were extracted from the Georgian Birth Registry (GBR) and the national vital registration system. All mothers who had singleton bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The proportion of women attending four ANC visits and initiating ANC before GA week 12 is increasing; however, these numbers are still far from Georgia’s target of 100% by 2030 [ 24 ]. Our previous study showed that women who did not attend any ANC visits during pregnancy had two-fold higher odds of PM compared to women who attended at least one ANC visit [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of women attending four ANC visits and initiating ANC before GA week 12 is increasing; however, these numbers are still far from Georgia’s target of 100% by 2030 [ 24 ]. Our previous study showed that women who did not attend any ANC visits during pregnancy had two-fold higher odds of PM compared to women who attended at least one ANC visit [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it is encouraging to observe that being a medical professional and receiving education on constipation during pregnancy were independently associated with higher knowledge scores. This suggests that healthcare providers can play a crucial role in disseminating accurate information to pregnant women, potentially by integrating essential education into routine antenatal care ( 22 , 23 ). Nevertheless, despite this generally positive trend, certain groups displayed a less favorable attitude, notably pregnant women in later stages of pregnancy and those who have experienced constipation during pregnancy or before.…”
Section: Discussionmentioning
confidence: 99%
“…Both antenatal care (ANC) and childbirth in hospitals are covered by the government. Hence, most women (99.8% in 2021) deliver in a birth facility and have at least one ANC visit during pregnancy (94.4%) [1,2]. Georgia has reached the millennium development goal for under-5 child mortality, but the infant (9.0 per 1,000 live births in 2021) and perinatal (10.9 per 1,000 births in 2021) mortality rates remain among the highest in Europe [1].…”
Section: Introductionmentioning
confidence: 99%